Youth perspective on pulmonary tuberculosis parent’s care - Kristina Lisum; Agung Waluyo; Astuti Yuni Nursasi; Jesika Pasaribu (International Journal of Public Health Science (IJPHS), 2022)
When parents have pulmonary tuberculosis (TB), youth can provide attentiveness to parent’s physical need and TB treatment. The purpose of this study was to determine the response of youth whose parents suffer from pulmonary TB. This research used descriptive qualitative design. Semi-structured interviews were conducted online and/or face-to-face in November 2020 to June 2021. There were 17 participants contributed to this study consisting of seven youth and seven parents or older siblings with pulmonary TB at Bogor regency. The data obtained were further analyzed using thematic analysis. Four thematics were produced from this research. These themes include knowledge of youth and parents with pulmonary TB: the transmission, administration duration, and side effects of TB medication; negative responses of youth to parents with pulmonary TB; youth poor skills in taking care for families; and cooperation between family, and health care workers in supporting the healing of pulmonary TB. Future research could develop and strengthen youth capacity to increase their skills providing care to parents with pulmonary TB.